Spatial scaling of forest soil microbial communities across a temperature gradient. (2nd September 2018) - Deng, Ye; Ning, Daliang; Qin, Yujia; Xue, Kai; Wu, Liyou; He, Zhili; Yin, Huaqun; Liang, Yuting; Buzzard, Vanessa; Michaletz, Sean T.; Zhou, Jizhong
Summary: Temperature is an important correlate of global patterns of biodiversity, yet the mechanisms driving these relationships are not well understood. Taxa‐area relationships (TARs) have been intensively examined, but the effects of temperature on TARs, particularly for microbial communities, are largely undocumented. Here we present a continental‐scale description of temperature‐dependent nested TARs of microbial communities (bacteria and archaea) from soils of six forest sites spanning a temperature gradient from subalpine Colorado to tropical Panama. Our results revealed that spatial scaling rates ( z ‐values) of microbial communities varied with both taxonomic resolutions and phylogenetic groups. Additionally, microbial TAR z ‐values increased with temperature ( r = 0.739, P < 0.05), but were not correlated with other environmental variables tested ( P > 0.05), indicating that microbial spatial scaling rate is temperature‐dependent. Understanding how temperature affects the spatial scaling of microbial biodiversity is of fundamental importance for preservation of soil biodiversity and management of ecosystems.